Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-78646-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Discounted Cumulated Gain Based Evaluation of Multiple-Query IR Sessions

Abstract: Abstract. IR research has a strong tradition of laboratory evaluation of systems. Such research is based on test collections, pre-defined test topics, and standard evaluation metrics. While recent research has emphasized the user viewpoint by proposing user-based metrics and non-binary relevance assessments, the methods are insufficient for truly user-based evaluation. The common assumption of a single query per topic and session poorly represents real life. On the other hand, one well-known metric for multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 8 publications
0
96
0
Order By: Relevance
“…Their information needs may initially be muddled and change during the search process; they may learn as the session progresses, or switch focus. The initial query formulation may not be optimal and the searchers may need to try out different wordings [2]. In fact, it may be impossible for the searcher to predict how well the query will perform [7] because even if the query describes the topic well, it may be ambiguous [8] and retrieve documents not serving the particular information need.…”
Section: User Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…Their information needs may initially be muddled and change during the search process; they may learn as the session progresses, or switch focus. The initial query formulation may not be optimal and the searchers may need to try out different wordings [2]. In fact, it may be impossible for the searcher to predict how well the query will perform [7] because even if the query describes the topic well, it may be ambiguous [8] and retrieve documents not serving the particular information need.…”
Section: User Behaviormentioning
confidence: 99%
“…The stopping decisions regarding browsing the retrieved documents depend on the search task and the individual performing the task [2]. Jansen and colleagues [1] observed that most users did not access results beyond the first page, i.e., the top-10 results retrieved.…”
Section: User Behaviormentioning
confidence: 99%
See 3 more Smart Citations